2012
DOI: 10.18433/j3cc86
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Adverse Drug Reactions Caused by Drug-Drug Interactions in Elderly Outpatients: A Prospective Cohort Study

Abstract: Purpose. The primary objective of this study was to investigate the incidence of drug-drug interactions (DDIs) related to adverse drug reactions (ADRs) in elderly outpatients who attended public primary healthcare units in a southeastern region of Brazil. The secondary objective was to investigate the possible predictors of DDI-related ADRs. Methods. A prospective cohort study was conducted between November 1, 2010, and November 31, 2011, in the primary public healthcare system in the Ourinhos micro-region in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 23 publications
1
21
1
2
Order By: Relevance
“…Of the 47 records resulting from the search strategies, 24 (51.1%) full-text articles were retrieved for review concerning ADR 11 - 18 , 20 , 24 - 25 , 28 - 29 , 34 - 36 , 38 - 40 , 46 , 51 - 52 , 54 , 56 ) , 14 (29.8%) DDI 21 - 23 , 27 , 30 - 33 , 41 , 43 - 45 , 49 , 53 and nine (19.1%) are related to both DDI and ADR 19 , 26 , 37 , 42 , 47 - 48 , 50 , 55 , 57 , according to Figures 2 and 3.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 47 records resulting from the search strategies, 24 (51.1%) full-text articles were retrieved for review concerning ADR 11 - 18 , 20 , 24 - 25 , 28 - 29 , 34 - 36 , 38 - 40 , 46 , 51 - 52 , 54 , 56 ) , 14 (29.8%) DDI 21 - 23 , 27 , 30 - 33 , 41 , 43 - 45 , 49 , 53 and nine (19.1%) are related to both DDI and ADR 19 , 26 , 37 , 42 , 47 - 48 , 50 , 55 , 57 , according to Figures 2 and 3.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of DDI was estimated from studies from similar (low-and-middle-income country) settings as in Trinidad. It is not clear whether prescribing and health-seeking behaviours would have been similar in these populations, but we considered these setting the best approximation to what was likely to be found in our study [ 3 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Al-Olah in Saudi Arabia further concluded that 83% of the adverse drug effects seen in Emergency Department patients were avoidable [ 2 ]. While the demographics of some of these countries, such as Brazil, may be similar to that seen in the West Indies, it is unclear whether health behaviour and prescribing are comparable [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that patients at the end of life are taking, on average, five medications, the number increasing as death approaches2 with symptom-specific medication accounting for 49% 3. The number of different medications taken is the strongest risk factor for symptomatic DDIs 4 5. For example, a recent study in regional Australia of patients being admitted to a palliative care centre showed that over one-fifth were still taking a lipid-lowering medication 6.…”
Section: Introductionmentioning
confidence: 99%